2007
DOI: 10.1021/jp070531a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Formation of Dark State via Depleted Spontaneous Emission in a Complex Solvated Molecule

Abstract: We present a general two-color two-pulse femtosecond pump-dump approach to study the specific population transfer along the reaction coordinate through the higher vibrational energy levels of excited states of a complex solvated molecule via the depleted spontaneous emission. The time-dependent fluorescence depletion provides the correlated dynamical information between the monitored fluorescence state and the SEP "dumped" dark states, and therefore allow us to obtain the dynamics of the formation of the dark … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…To know the detail information about the mechanism of excitation delocalization, charge localization, and nature of ICT in these series of compounds, transient measurement should be very useful. In our lab, femtosecond time-resolved fluorescence depletion technique has been proven to be a powerful method to determine the fast solvation processes of similar push-pull molecules in our earlier investigations [14,15,22], within our experimental conditions time resolution down to 200 fs has been achieved. However, predicted by both theoretical calculations and dynamic results, it is known that the ICT emitting state may delocalize some extent among the branches possessing a relatively weaker coupling with the bath in nonpolar solvent, which can be strongly affected in polar solvent [24].…”
Section: E Femtosecond Fluorescence Depletionmentioning
confidence: 86%
See 1 more Smart Citation
“…To know the detail information about the mechanism of excitation delocalization, charge localization, and nature of ICT in these series of compounds, transient measurement should be very useful. In our lab, femtosecond time-resolved fluorescence depletion technique has been proven to be a powerful method to determine the fast solvation processes of similar push-pull molecules in our earlier investigations [14,15,22], within our experimental conditions time resolution down to 200 fs has been achieved. However, predicted by both theoretical calculations and dynamic results, it is known that the ICT emitting state may delocalize some extent among the branches possessing a relatively weaker coupling with the bath in nonpolar solvent, which can be strongly affected in polar solvent [24].…”
Section: E Femtosecond Fluorescence Depletionmentioning
confidence: 86%
“…Fitting results are listed in Table IV. It is found that a fast decay with a few hundred femtosecond attributed to the vibration relaxation of the monitored emitting states and a slow decay with several picoseconds attributed to solvation dynamics related to the formation of the final relaxed ICT state, respectively [14,15,22]. Here, since both polarity and viscosity affect the solvation dynamic processes, we compare solvation assisted ICT dynamics of the three compounds in the same solvent.…”
Section: E Femtosecond Fluorescence Depletionmentioning
confidence: 98%
“…The same effect was observed in a few push–pull D – π – A salts and it has also a practical application 42. The evidence of the final relaxed nonluminiscent dark TICT state in the commercial benzothiazolium push–pull laser dye LDS 751 (which is structurally very close to dye 2 ) was recently confirmed experimentally using the FS TR SEP FD method (femtosecond time resolved stimulated emission pumping fluorescence depletion) 43. Hydrogen bonding effect of the solvent can also contribute to the nonradiative internal conversion 41…”
Section: Resultsmentioning
confidence: 85%
“…We distinguished fast ( τ 1 ) and slow ( τ 2 ) decay times of approximately 80 ± 10 ns and 1.3 ± 0.1 µs, respectively, with the short component fractional yield of ∼70–75% from the biexponential fits. The short component of the luminescence signal is assumed to result from a deactivation of the dark TICT state43 or it may be as well a component of phosphorescence. However, the second alternative is quite unusual for most organic triplets.…”
Section: Resultsmentioning
confidence: 99%
“…1) in the first and higher excited states in aprotic polar solvents, namely, acetone, dimethylformamide (DMF), dimethylsulfoxide (DMSO). This method has been used to study the ultrafast vibrational and rotational relaxation in solution [34][35][36][37][38][39][40][41][42][43]. A quantitative analysis of the experimentally measured reorientation time was carried out using the SED theory combined with the extended charge distribution model developed by Alavi and Waldeck (AW) [44,45].…”
Section: Introductionmentioning
confidence: 99%